P3.120 Prevalence of ureaplasma urealyticum in urine of men attending a sexually transmitted disease clinic. (8th July 2017) - Fife, Kenneth; Williams, James A; Fortney, Sarah; Qadadri, Brahim; Ermel, Aaron
Abstract : Introduction: Ureaplasma urealyticum (UU) is probably one of the causes of non-gonococcal, non-chlamydial urethritis in men and post-partum endometritis in women. The epidemiology of UU is currently unclear because culture isolation is difficult and molecular identification is limited to specialised laboratories. Testing for UU would be useful for surveillance, disease management, and epidemiology. This study assessed the prevalence of UU in men attending the local STD clinic by real-time PCR. Methods: A convenience sample of de-identified residual urine specimens from men attending an STD clinic was collected. Urine was placed into commercially available transport tubes and tested by PCR for Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), and Trichomonas vaginalis (TV). The remaining residual processed specimen was tested for UU DNA using a previously published real-time PCR assay. Descriptive statistics were used to examine UU prevalence with age, and co-infection with CT, NG, and TV. Results: A total of 99 residual male urine specimens were available for testing. UU DNA was detected in 16/99 (16.2%) of the specimens and was comparable to CT (14/97, 14.4%), NG (11/97, 11.3%), and TV (4/25, 16.0%). Of the 16 UU positive specimens, co-infection with CT was observed in one (6.25%), NG in one (6.25%), and the remaining 14 (87.5%) had no other infection identified. The mean age of those individuals positive for UU DNA was 32.4 (range 18–63) while the mean age of those infected with CT, NG, and TV was 29.8, 28.3, and 36.8 years old, respectively. Conclusions: The prevalence of UU in men attending an STD clinic is similar to that observed for CT, NG, and TV. This study was useful in order to gain a better understanding of UU in this population including the age of those positive for UU, co-infection status with other commonly identified pathogens, and as a means to confirm the feasibility of real-time PCR testing using residual processed specimens. More studies are needed to elucidate the significance of UU in this population.